Efficacy of intravenous immunoglobulin treatment in refractory uveitis - (:unkn) unknown (TAYLOR & FRANCIS INC, 2006)
Purpose: To assess the efficacy of intravenous immunoglobulin (IVIg) therapy in patients with severe uveitis otherwise unresponsive to conventional immunomodulatory agents. Methods: Data on five consecutive patients treated with IVIg and followed to the present time by one of the authors (CSF) were reviewed. All patients had severe and recalcitrant uveitis of diverse etiologies. Main outcome measures were control of intraocular inflammation, steroid-sparing effect, visual acuity, and side effects. Results: The duration of IVIg therapy was 3 to 36 months ( mean, 16.8 months). Treatment was effective in controlling the intraocular inflammation in 3 of 5 patients. One of those patients required maintenance of systemic steroids at a dose of 10 mg per day. Visual acuity has stabilized or improved in these three patients. No immediate or long-term side effect was observed in any of the patients. Conclusions: Intravenous immunoglobulin therapy was an effective therapeutic modality in the treatment of three of five patients with severe uveitis that was unresponsive to conventional immunomodulatory agent(s). No adverse events were observed.
Keywords: intravenous immunoglobulin; uveitis; refractory; GAMMA-GLOBULIN TREATMENT; IMMUNE GLOBULIN; THERAPY